Percutaneous coronary intervention using rotational atherectomy and new-generation drug-eluting stents in mild versus moderate-to-severe chronic kidney disease patients with coronary artery disease - Fazila-Tun-Nesa Malik; Md Kalimuddin; Nazir Ahmed; Mohammad Badiuzzaman; Abdul Kayum Khan; Ashok Dutta; Tawfiq Shahriar Huq; Dhiman Banik; Mir Nesaruddin Ahmed; Md Habibur Rahman; Md Abu Tareq Iqbal (Journal of Indian College of Cardiology, 2021)
Background: The presence of calcified lesions in chronic kidney disease (CKD) patients adversely affects the outcomes of percutaneous coronary interventions (PCIs). Lesion modification using rotational atherectomy (RA) followed by drug-eluting stent (DES) implantation may, therefore, be a suitable strategy to treat heavily calcified coronary lesions in CKD patients. Aim: The aim of the study was to compare the effectiveness and safety of PCI using RA and new-generation DES for treating calcified coronary lesions in patients with mild versus moderate-to-severe CKD. Methods: This was a single-center, retrospective study. Data were collected from the medical records of all CKD patients with calcified coronary artery lesions who underwent RA + DES implantation from November 2014 to October 2019. The primary outcomes were the rates of in-stent restenosis (ISR), repeat revascularization (RR), and major adverse cardiovascular and cerebrovascular events. Secondary outcomes included procedural success, death after intervention, and procedural/in-hospital complications. Results: A total of 77 and 126 patients with mild and moderate-to-severe CKD were treated with RA + DES. Patients with moderate-to-severe CKD were significantly older when compared to patients with mild CKD (mean age: 66.6 ± 8.2 vs. 59.5 ± 7.7 years, respectively, P < 0.0001). Body mass index was significantly lower in moderate-to-severe CKD group compared to the mild CKD group. The number of patients in whom postdilatation was performed after stent implantation was significantly higher in the moderate-to-severe CKD group compared to the mild CKD group (100% vs. 96%, P = 0.025). Overall procedural success was 97.5% with minimal periprocedural complications. The rates of ISR and RR were not significantly different between patients with mild and moderate-to-severe CKD. The two groups did not differ significantly in terms of procedural success, postprocedural complications, and procedural mortality. Conclusion: RA followed by DES implantation is an effective and safe strategy to treat calcified coronary artery lesions in patients with CKD, regardless of the degree of renal dysfunction.